Hubungan Antara Risiko Postur Kerja Dengan Risiko Keluhan Muskuloskeletal Pada Pekerja Di Bagian Produksi Tenun PT. Kusuma Mulia Plasindo Infitex Klaten - Utami Wulandari, Dewi; , Tarwaka, PGDip.Sc., M.Erg (2016)
One of the risks of musculoskeletal diseases is caused by unnatural posture of working activity.The purpose of this research is to know the relation between posture risk and risk of musculoskeletal complaints at weaving section in PT . Kusuma Mulia Plasindo Infitex Klaten. The type of research which is applied in this research is observational analytic type by cross sectional approach. The number of samples in this research are 76 respondents who were taken by using proportional random sampling techniques. The statistical tests are using the Spearman Rho test along with SPSS 20. The results showed that there is a relationship between the risk of working posture and the risk of musculoskeletal complaint p-value 0.000 means p <0.05 with a high level of closeness relation (r = 0.625). It is recommended that the workers must be able to improve the attitude or position activity during their works. Keywords: musculoskeletal complaints, work posture.